Demonization in Politics - Buksiński, Tadeusz (Sensus Historiae, 2024)
The article highlights the growing significance of the phenomenon of demonization in contemporary political and public life. Demonization is no longer limited to extremely evil events (such as the Holocaust) or individuals (like Hitler and Stalin), but it increasingly extends to more common occurrences and “normal” politicians. Politically exploited, demonization is used to discredit politicians and events. Demonization hinders rational dialogue and understanding among political rivals in democratic systems, making it a socially perilous phenomenon. Some philosophers, Hannah Arendt in particular, engage in combating this phenomenon.